Marine Plastic Pollution Handling Based on International and Indonesian Law to Support Sustainable Development Goals - Aryuni Yuliantiningsih; Ade Maman Suherman; Baginda Khalid Hidayat Jati (UNIFIKASI : Jurnal Ilmu Hukum, 2023)
Due to the increasing level of marine plastic pollution, the handling to preserve and protect the sea is urgently needed. Accordingly, this study discusses about the handling of marine plastic pollution based on international and Indonesian law. The normative juridical research method with a statute and analytical approach was used to analyze the secondary data descriptively. Based on the analysis, it was known that the prevention and handling of marine plastic pollution have not been specifically regulated in international law, both in hard law and soft law. Yet, there was a UNEA Resolution 4/15 of 2022 promoting the formation of international agreements to handle plastic pollution. Meanwhile, in Indonesian law, the handling of marine plastic pollution is generally regulated in the Law of the Sea. Specifically, it was regulated in Presidential Regulation No. 2018 on Marine Debris Management which is complemented by a National Plan of Action from 2018-2025 to reduce up to 70% of plastic debris in the sea. Efforts to prevent and handle marine plastic pollution at international and national levels are in line with the 14th SDGs target to protect the sea from pollution.